The AKT inhibitor, MK-2206, attenuates ABCG2-mediated drug resistance in lung and colon cancer cells - Hai-Ling Gao; Qingbin Cui; Jing-Quan Wang; Charles R. Ashby; Yanchun Chen; Zhi-Xin Shen; Zhe-Sheng Chen (Frontiers Media S.A., 2023)
Introduction: The overexpression of ATP-binding cassette (ABC) transporters, ABCB1 and ABCG2, are two of the major mediators of multidrug resistance (MDR) in cancers. Although multiple ABCB1 and ABCG2 inhibitors have been developed and some have undergone evaluation in clinical trials, none have been clinically approved. The compound, MK-2206, an inhibitor of the protein kinases AKT1/2/3, is undergoing evaluation in multiple clinical trials for the treatment of certain types of cancers, including those resistant to erlotinib. In this in vitro study, we conducted in vitro experiments to determine if MK-2206 attenuates multidrug resistance in cancer cells overexpressing the ABCB1 or ABCG2 transporter.Methodology: The efficacy of MK-2206 (0.03-1 μM), in combination with the ABCB1 transporter sub-strates doxorubicin and paclitaxel, and ABCG2 transporter substrates mitoxantrone, SN-38 and topotecan, were determined in the cancer cell lines, KB-C2 and SW620/Ad300, which overexpress the ABCB1 transporter or H460/MX20 and S1-M1-80, which overexpress the ABCG2 transporter, respectively. The expression level and the localization of ABCG2 transporter on the cancer cells membranes were determined using western blot and immunofluorescence assays, respectively, following the incubation of cells with MK-2206. Finally, the interaction between MK-2206 and human ABCG2 transporter was predicted using computer-aided molecular modeling.Results: MK-2206 significantly increased the efficacy of anticancer compounds that were substrates for the ABCG2 but not the ABCB1 transporter. MK-2206 alone (0.03-1 μM) did not significantly alter the viability of H460/MX20 and S1-M1-80 cancer cells, which overexpress the ABCG2 transporter, compared to cells incubated with vehicle. However, MK-2206 (0.3 and 1 μM) significantly increased the anticancer efficacy of mitoxantrone, SN-38 and topotecan, in H460/MX20 and S1-M1-80 cancer cells, as indicated by a significant decrease in their IC50 values, compared to cells incubated with vehicle. MK-2206 significantly increased the basal activity of the ABCG2 ATPase (EC50 = 0.46 μM) but did not significantly alter its expression level and sub-localization in the membrane. The molecular modeling results suggested that MK-2206 binds to the active pocket of the ABCG2 transporter, by a hydrogen bond, hydrophobic interactions and π-π stacking.Conclusion: These in vitro data indicated that MK-2206 surmounts resistance to mitoxantrone, SN-38 and topotecan in cancer cells overexpressing the ABCG2 transporter. If these results can be translated to humans, it is possible that MK-2206 could be used to surmount MDR in cancer cells overexpressing the ABCG2 transporter.